2016
DOI: 10.1007/s10453-016-9425-7
|View full text |Cite
|
Sign up to set email alerts
|

Warm and dry weather accelerates and elongates Cladosporium spore seasons in Poland

Abstract: Temperature is the environmental factor that systematically changes for decades and, as in plants and animals, can significantly affect the growth and development of fungi, including the abundance of their sporulation. During the time of study (2010–2012), a rapid increase in air temperature was observed in Poland, which coincided with the substantial decrease in rainfall. The increase in annual mean temperatures at three monitoring sites of this study was 0.9 °C in Lublin and Rzeszow (east Poland) and 2.0 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 38 publications
2
9
2
2
Order By: Relevance
“…The monthly SIns, the number of days with average concentration above 3,000 Spores m -3 , and the value of the peak concentrations in Viborg were lower compared with the values reported from Poland (Kasprzyk et al 2016;Grinn-Gofroń and Mika 2008), England (Sadyś et al 2016), and France (Sindt et al 2016) but higher than those found in Morocco (Bardei et al 2017), Croatia (Peternel et al 2003) and northern Portugal (Oliveira et al 2009). The climatic conditions and the type of land cover determine both the availability of organic material in the form of vegetation, that is prerequisite nutrient for fungi, and the growth of fungi mycelium leading to sporulation.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The monthly SIns, the number of days with average concentration above 3,000 Spores m -3 , and the value of the peak concentrations in Viborg were lower compared with the values reported from Poland (Kasprzyk et al 2016;Grinn-Gofroń and Mika 2008), England (Sadyś et al 2016), and France (Sindt et al 2016) but higher than those found in Morocco (Bardei et al 2017), Croatia (Peternel et al 2003) and northern Portugal (Oliveira et al 2009). The climatic conditions and the type of land cover determine both the availability of organic material in the form of vegetation, that is prerequisite nutrient for fungi, and the growth of fungi mycelium leading to sporulation.…”
Section: Discussioncontrasting
confidence: 74%
“…Cladosporium conidia belong to the so-called dry spores, as higher temperatures and absence of precipitation have been frequently observed to facilitate the increase in their air concentrations (Kasprzyk et al 2016;Aira et al 2012). The value of spearman correlation coefficient for the T mean found in this study is comparable to the reported previously, and despite the absence of correlation with precipitation, the highest concentrations of spores were observed on the dry days.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is clearly visible in this study. Data analysis revealed the fact that daily mean temperature was the most important meteorological parameter positively affecting Cladosporium spore concentrations in the air (Kasprzyk et al, 2016). A decrease in spore concentration was related to increasing maximum temperature.…”
Section: Discussionmentioning
confidence: 96%
“…Este tiene un desarrollo óptimo entre 20 y 28 ºC, valores de temperatura que se alcanzan en estos períodos poco lluviosos. Varios autores han planteado que la temperatura influye notablemente sobre la biología de este género (Grinn-Gofron y Bosiacka 2015, Kasprzyk et al 2016). En Rumanía, Ianovici (2016) comprobó que esta variable meteorológica tenía una fuerte influencia sobre su concentracion en el aire.…”
Section: Discussionunclassified